Green and blue infrastructure design in a semi-arid region - Bel Fekih Boussema, Safa; Cohen, Marianne; Khebour Allouche, Faiza (Frontiers in Environmental Science, 2022)
The Green and Blue Infrastructure (GBI) is a new approach dealing with biodiversity conservation based on the maintenance of the ecological network whose aim is to ensure the survival of animal and plant species. It is considered a new public policy to avoid the loss of biodiversity by persevering the landscape connectivity and natural habitats from fragmentation. For example, different countries like the United States, Canada, United Kingdom, Italy, Portugal, Japan, China, Brazil, and Turkey are trying to integrate this concept into their environmental policies. This research proposes a methodology to design a GBI at a regional scale applied to the Sousse region in Tunisia. Two main approaches are used; the first is based on identifying three referenced species marked by different dispersal distances. The second deals with GIS spatial analysis using the buffer model which will help us to assess the ecological connectivity. The methodology developed comprises five steps. In the first step, a forest habitats sub-frame, a semi-open habitats sub-frame, and a wetlands sub-frame were determined from a detailed land-use map. Then, different reservoirs of biodiversity were identified. In the third step, buffers varying between 200, 250, and 300 meters depending on the dispersal distance of reference species such as Cape hare, North African Hedgehog, and Marbled Teal were applied around the reservoirs in order to identify zones of potential connections between them. Next, buffers were also applied to detect fragmentation zones along the road network and build-up areas. Finally, the ecological corridors were mapped from the overlay between zones of potential connections and the fragmentation map. As a result, the GBI of the Sousse region is created with reservoirs of biodiversity and ecological corridors that connect them. Thus, the methodological approach developed and the characterization of the Sousse city GBI map represents the first innovative research applied in Tunisia. This prototype can be a reference to other local or regional spaces, contributing toward realizing a national GBI and promoting sustainable projects.